Psychological diagnostic of risk factors for involving adolescents in the use of narcotic substances: the development of a methodical complex. Part 2. Criterion validity and analysis of profles - E. G. Demenko; E. I. Rasskazova; A. Sh. Tkhostov; E. A. Brun; B. V. Arshinova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Te second part of the paper presents the results of testing the criterion validity of the methodological complex scales conducted on a sample of 637 pupils of the upper grades of general education schools from 12 constituent entities of the Russian Federation and 108 pupils involved in the use of narcotic substances. Pupils using narcotic substances are characterized by a tendency to technological addictions, antisocial tendencies, difculties in self-regulation accompanied by overestimation of the own ability to control emotions, denying the interest for novelty, risky behavior and avoidance as well as difculties in child-parent relations. Some of these factors are manifested in those with a protective response strategy and others — in those with an open demonstration of difculties, which allows us to separate the two risk profles. In pupils appraising their ability to control emotions as high, the risk of involvement in the use of narcotic substances is associated with either a demonstrating or an illusory excessively «prosperous» profle: an overestimation of own emotional control and social support, denial of avoidance, denial of interest for novelty and risky behavior. In pupils appraising their ability to control emotions as low, the risk is higher in those with higher rates of technological addictions, antisocial tendencies, difculties in self-regulation and in child-parent relationships.